PENGARUH LKPD INOVATIF BERBASIS INQUIRY TERHADAP HASIL BELAJAR SISWA PADA TEMA 7 SUBTEMA 2 KELAS VI SD NEGERI 060856 KECAMATAN MEDAN PERJUANGAN T.A 2023/2024 - Marintan Evelyn Marbun (Universitas Negeri Medan, 2024)
Abstract: The Effect of Innovative Inquiry-Based Student Worksheets on Student Learning Outcomes in Theme 7 Subtheme 2 of Grade VI of Elementary School 060856, Medan Perjuangan District, Academic Year 2023/2024. The purpose of this study was to determine whether or not there was an effect of innovative inquiry-based student worksheets on student learning outcomes in theme 7 subtheme 2